Longitudinal Impacts of Forest Loss on Bartonella and Hemotropic Mycoplasma Dynamics in Vampire Bats Within a Fragmented Habitat - Lauren R. Lock; Kristin E. Dyer; Dmitriy V. Volokhov; Anni Yang; M. Brock Fenton; Nancy B. Simmons; Daniel J. Becker (Molecular Ecology, 2026)
Habitat fragmentation can negatively impact wildlife, including increasing infectious disease risk. We assessed spatiotemporal changes in pathogen dynamics in vampire bats ( Desmodus rotundus ) in response to habitat fragmentation using general linear mixed models to investigate the influence of site, year, and tree cover on Bartonella spp. and hemotropic Mycoplasma spp. (hemoplasmas) infection risk in bats in one large and one small forest fragment in Belize across seven years. While Bartonella infections were more likely in the final years of the study regardless of site, hemoplasma infection likelihood was not significantly different across years or sites. Bartonella infections were associated with increased forest loss in the large fragment only, whereas hemoplasma infections were not associated with forest loss. The effects of site, year, and forest loss on infection likelihood varied by pathogen genotype despite low model explanatory power. Neither site nor year was associated with bartonellae, but one genotype was positively associated with tree cover. Two hemoplasmas were influenced by year with differing trends: one genotype was negatively associated with tree loss across sites, while another was positively associated with forest loss at the small fragment only. Both pathogens were similarly influenced by bat demographics and showed instances of infection status and genotype switching. Our work suggests that the effects of habitat fragmentation on infection risk depend on both the pathogen and specific genotype, complicating expectations of how environmental change affects wildlife disease dynamics. Efforts to mitigate infectious disease impacts in fragmented systems should be tailored to specific pathogens of concern.